Incorporation of Latino Police Officers into the Milwaukee Police Department: How a Group of Latino Police Officers Shed the "Blue Shield" for a Latino Identity - (:unkn) unknown (My University, 2015)
ABSTRACT INCORPORTATION OF LATINO POLICE OFFICERS INTO THE MILWAUKEE POLICE DEPARTMENT: HOW A GROUPS OF LATINO POLICE OFFICERS SHED THE “BLUE SHIELD” FOR A LATINO IDENTITY by Antonio G Guajardo Jr. The University of Wisconsin Milwaukee 2015 Under the Supervision of Professor Joe Rodriguez This study examines the issue of ethnic identity and its importance to the Latino police officers in the MPD. The study also explores the relationship between these officers and Milwaukee’s Latino communities, analyzing historical incidents of activism within these communities meant to pressure the Department into hiring Latino officers. It also examines the officers’ experiences and views regarding the importance of their ethnic identities and their identities as professional law enforcers. The study also historically analyzes the organizations formed by the Latinos officers, the National Latino Peace Officers Association (NLPOA) and their effect on the police subculture within the MPD. The study reveals that identity was an important factor in their professional experiences for the Latino Peace Officers Association interviewed. Further, the organizations they formed, the National Latino Peace Officers Association, had an impact on the influence of the police subculture. The NLPOA helped Latino officers pull away from the police subculture, shedding the “Blue Shield,” moving to identifying with the Latino community.
Keywords: Latino; Mexican American; Police Subculture; Policing; Ruerto Ricans